Self-directed learning competencies as a prerequisite for knowledge management in open learning resources: e-learning platform case - Poceviciene, Rasa (Encontros da Licenciatura em Ciências e Tecnologias da Documentação e Informação, 2022)
Development of E-Learning and various of E-learning platforms as well as the development of information and communication technologies in general, is so fast that there is almost no doubt that sooner or later they will become the routine for each of us. Information and communication technologies have not only expanded our ability to access, manage, disseminate information, but also to do this very quickly, over long distances and in even huge quantities. Today, their application in the educational process is not only relevant to the aspects of visualization or activation. They become one of the essential tools of teaching and learning activities in the 21st century, but by expanding our learning opportunities they have also highlighted the need for new learning competences. The traditional roles of teacher and learner are replaced by new ones because in E-Teaching / learning environment, the learner must not only work independently, but also more and more often have to define learning goals, methods and activities, organize his / her learning, and so on. This requires that he has the competence of self-directed learning, which can be defined as readiness and ability to formulate individual learning goals independently; adjust them according to need and / or situation; plan and organize your learning process; to solve the various problems that arise during it; reflect on your own experience and evaluate the results and the process itself and, on the basis of those reflections, manage your further learning. The extent to which learners will have mastered this competence greatly depends on how much they will be able to and how qualitatively they will be able to benefit from the E-learning education. Obviously, one of the essential duties of today's teacher is to create, as far as possible, a learning environment that is educationally friendly, enabling, stimulating, motivating, and constructive. However, the extent to which each learner will take from that environment will depend only on his / her own, namely engagement, motivation, relevant skills and competences, especially selfdirected learning. Mastering this competence would not only lead to success in teaching / learning but would also largely save time and effort on learning. This competence is relevant for all ages, and the demand for adult learners is even greater. ; K;